Identification of Tenrec ecaudatus, a Wild Mammal Introduced to Mayotte Island, as a Reservoir of the Newly Identified Human Pathogenic Leptospira mayottensis. - Erwan Lagadec; Yann Gomard; Gildas Le Minter; Colette Cordonin; Eric Cardinale; Beza Ramasindrazana; Muriel Dietrich; Steven M Goodman; Pablo Tortosa; Koussay Dellagi (Public Library of Science (PLoS), 2016)
Leptospirosis is a bacterial zoonosis of major concern on tropical islands. Human populations on western Indian Ocean islands are strongly affected by the disease although each archipelago shows contrasting epidemiology. For instance, Mayotte, part of the Comoros Archipelago, differs from the other neighbouring islands by a high diversity of Leptospira species infecting humans that includes Leptospira mayottensis, a species thought to be unique to this island. Using bacterial culture, molecular detection and typing, the present study explored the wild and domestic local mammalian fauna for renal carriage of leptospires and addressed the genetic relationships of the infecting strains with local isolates obtained from acute human cases and with Leptospira strains hosted by mammal species endemic to nearby Madagascar. Tenrec (Tenrec ecaudatus, Family Tenrecidae), a terrestrial mammal introduced from Madagascar, is identified as a reservoir of L. mayottensis. All isolated L. mayottensis sequence types form a monophyletic clade that includes Leptospira strains infecting humans and tenrecs on Mayotte, as well as two other Malagasy endemic tenrecid species of the genus Microgale. The lower diversity of L. mayottensis in tenrecs from Mayotte, compared to that occurring in Madagascar, suggests that L. mayottensis has indeed a Malagasy origin. This study also showed that introduced rats (Rattus rattus) and dogs are probably the main reservoirs of Leptospira borgpetersenii and Leptospira kirschneri, both bacteria being prevalent in local clinical cases. Data emphasize the epidemiological link between the two neighbouring islands and the role of introduced small mammals in shaping the local epidemiology of leptospirosis.